Celestina ludens: La negociación del dolor desde la teoría de juegos y la fenomenología de la lectura en Celestina. - Mallorquí-Ruscalleda, Enric (Scripta, 2022)
In this paper, which recovers some of my previous foundational ideas on Celestina, I use game theory and the phenomenology of reading to analyze the different games that organize and structure Rojas’s (and “old author”) text. This allows me to demonstrate that strategy, negotiation and economy, always in relation to pain, are fundamental to understanding the text.